(untitled) (Texas Journal of Philology, Culture and History, 2026)
This article examines myth as a discursive mechanism that constructs “otherness” and contributes to the demonization of Amir Timur in Early Modern English literary discourse. Focusing primarily on Tamburlaine the Great by Christopher Marlowe, the study explores how mythological and symbolic elements reshape historical reality into a narrative of fear, excess, and cultural opposition. Drawing on postcolonial theory, particularly Orientalism by Edward Said, as well as discourse analysis, the research demonstrates how Timur is represented not as a complex historical figure but as an embodiment of the “Eastern Other.” The article argues that myth functions as an ideological tool that reinforces binary oppositions between East and West, civilization and barbarism. Ultimately, the study reveals how literary myth-making contributes to enduring cultural stereotypes and influences the reception of historical figures within Western literary tradition